Conducting mechanisms and magnetic behaviours of Fe-doped In₂O₃ nanocrystalline films - Hussein Baqiah, Hussein Abdullah; Ibrahim, N. B.; Shaari, Abdul Halim; Talib, Zainal Abidin; Flaifel, M. H.; Abdi, M. H. (Elsevier, 2017)
The relation between conducting mechanism and magnetic behaviour of Fe-doped In2O3 thin films was investigated. The films were prepared by sol gel method followed by spin coating techniques and characterized by X-rays diffractions, field emission electron microscopy, transmission electron microscopy, Hall Effect at room and low temperature, X-ray photoelectron spectroscopy and vibrating sample magnetometer. Films’ lattice parameter decreased with increasing of Fe content. Average grain size of films ranged between 8.4 and 13 nm. Oxygen vacancies of films tended to reduce with increasing of Fe doping. Films with x = 0.025 and 0.05 showed typical semiconducting behaviour while transition from metallic- to semiconducting-like behaviour was observed at 190 K and 230 K for films with x = 0.075 and x = 0.15, respectively. No trend had been found between films saturation magnetization, Ms, and free charge carriers. The magnetic behaviour of films has a correlation with localized electrons of Nearest-Neighbour Hopping conduction.